2022
DOI: 10.3390/foods11071012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Teff-Based Sourdoughs on Dough Rheology and Gluten-Free Bread Quality

Abstract: Production of gluten-free bread (GFB) with good quality characteristics represents a technological challenge. Our study aimed to obtain nongluten bread from cereals and pseudocereals with applying single cultures of Pediococcus acidilactici, Pediococcus pentosaceus and Enteroccocus durans as sourdoughs. The effect of sourdoughs on the quality traits of gluten-free (GF) dough and GFB was explored. The structural and baking properties of GF dough composed of teff, rice, corn, and sorghum flours were improved by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 101 publications
0
3
0
Order By: Relevance
“…The LAB strains used originated from typical Bulgarian sourdoughs and were selected as the best-performing strains in a previous research conducted on non-gluten sourdough bread preparation (Chochkov et al, 2022).…”
Section: Active Acidity (Ph) Total Titratable Acidity (Tta) and Lab V...mentioning
confidence: 99%
“…The LAB strains used originated from typical Bulgarian sourdoughs and were selected as the best-performing strains in a previous research conducted on non-gluten sourdough bread preparation (Chochkov et al, 2022).…”
Section: Active Acidity (Ph) Total Titratable Acidity (Tta) and Lab V...mentioning
confidence: 99%
“…The dough was then baked in an electric floor oven Salva E-25 (Salva Industrial S.L.U., Lezo, Spain), preheated to a temperature of 220 -230℃, for 22 -24 min. After baking, the breads were allowed to cool for 3 h at room temperature (Chochkov et al 2022). The bread formulations are given in Table 1.…”
Section: Preparation Of Dough and Bread Samplesmentioning
confidence: 99%
“…Chochkov et al [4] explored the effect of sourdoughs on the quality traits of gluten-free dough (composed of teff, rice, corn, and sorghum flours) and GF bread. They found that sourdough-fermented doughs were softer and more elastic compared to control dough and yielded reduced baking losses.…”
mentioning
confidence: 99%